"Leodum Lidost on Lofgeornost". La poesía épica de "Beowulf" en nuevos formatos gráficos y visuales - Bueno Alonso, Jorge Luis (2007)
The new formats we have nowadays for the transmission of knowledge are heavily modifying our relationship with the products of our culture. They al so give us new possibilities to deal with literary texts, which constitutes a very important step in the transmission of medieval literature through popular culture. In its age, Beowulf entertained the audience of the meadhall. lt was the best-seller of the day, the successful potboiler movie of Anglo-Saxon England. In our time its story of men and monsters has again attracted the attention of many talented graphic and visual artists that want to put the Beowulf tale back in its oral context, though these days that context belongs to the new visual orality of our early 21st Century mass culture. One of those artists, Gareth Hinds (2003), has faithfully followed the narrative content of Beowulf in his graphic novel The Collected Beowulf, a very interesting case of adaptation. The main aim of this article is to analyse the three features that turn this adaptation into the best graphic version published up till now: a) the text used in its narrative script; b) its narrative structure and plot development; and c) its conceptual design. If we relate these aspects to the structure of Beowulf as a literary text, we'll see how these new formats -out of which graphic novels constitute outstanding examples- maintain the new generations' interest in old literary texts and serve as proper vehicles to carry out the retelling of an old story for a new audience.
Keywords: Poesía épica; Transmisión de textos